Portuguese media startups lead in innovation and get closer to audiences - Crespo, M.; Paisana, M.; Pinto-Martinho, A.; Foá, C.; Pais, Pedro Caldeira (Broadcast Education Association 2022 Conference, 2022)
Innovation plays a significant role in the evolution and consolidation of any media landscape. Despite their smaller size and influence when compared to historic and legacy brands, news media startups form a unique ecosystem for innovation, materialized by a wide range of journalistic, managerial, and business practices. Whether by the adoption of different business models, unique strategies of financing journalism, new ways of producing content or targeting niche audiences, the Portuguese news media startup scene is challenging industry standards and setting new benchmarks for the sector as a whole, legacy brands included.